Economic optimum in a bivariate Cobb-Douglas function: an application to semi-extensive beef farming - Martinez Damian, Miguel Angel; Rebollar-Rebollar, Samuel; Hernández-Martínez, Juvencio; Hernández-Aguirre, Pedro (Revista Mexicana de Ciencias Agrícolas, 2021)
The objective of this research is to determine the economic optimum when the production technology is such that the marginal product of an input is not separable from the use of other inputs. With field information from 51 producers of beef cattle under semi-extensive conditions, surveyed during February-July 2015, in the south of the State of Mexico and obeying a production simplification to two inputs to avoid expressions of marginal products not analytically treatable, the economic optimum for two inputs was obtained, concluding that the intensity of use of this optimum is greater than 30% of the average use in the sample.
Keywords: beef cattle; economic optimum; net income; semi-extensive